Implementation of the Family Hope Program (PKH) in Supporting Community Access to Education in Botuboluo Village, Biluhu District, Gorontalo Regency - Acun H. Tooli; Yakob Noho Nani; Rahmatia Pakaya (CV. Edujavare Publishing, 2026)
This study examines the implementation of the Family Hope Program (PKH) in supporting community access to education in Botuboluo Village, Biluhu District, Gorontalo Regency. Poverty remains a major social issue in Indonesia, limiting people’s access to basic needs, particularly education and health services. Therefore, PKH was implemented as a conditional cash transfer program to improve the welfare of poor households and increase access to education. The purpose of this study was to analyze the planning, implementation, and evaluation of PKH management in supporting educational access for beneficiary families. This research employed a qualitative approach using primary and secondary data obtained through interviews, observation, and documentation. Informants included village government officials, PKH facilitators, and beneficiary families. Data were analyzed using qualitative data reduction, display, and conclusion drawing techniques. The findings revealed that PKH implementation in Botuboluo Village has contributed positively to improving school attendance, educational access, and community welfare. However, several challenges remain, including inaccuracies in beneficiary targeting, limited coordination, administrative constraints, and the potential dependency of beneficiaries on social assistance. The study concludes that the effectiveness of PKH is influenced by the integration of formal data systems, local social validation, implementation capacity, and continuous monitoring mechanisms.